It's an Ad, Ad, Ad World - Strategies of tobacco industry in India to diffuse tobacco control efforts- An unholy nexus - Sonu Goel; Pranay Lal (Wolters Kluwer Medknow Publications, 2016)
World Health Organization (WHO) recommends prohibition of advertisements, promotion and sponsorship of tobacco to reverse tobacco epidemic. Tobacco advertising, promotion and sponsorship (TAPS) is also banned under India's Cigarettes and Other Tobacco Products Act, 2003, with few exceptions. Despite the Act and increasing evidence of advertising linked with smoking behaviours, tobacco companies indulge in it brazenly to neutralise tobacco control efforts and normalize its use, making it seem like any other consumer product. The companies aim at creating a brand franchise for their product through advertisements. Point of sale promotion account for more than three-fourth of marketing spends by tobacco companies. Although India has been a frontrunner in tobacco control, it faced huge legal challenge from the tobacco industry. There is a need to regulate tobacco business by compulsory registration and licensing of tobacco vendors and also effective implementation of Indian Act. Besides, the gap in current research from developing countries on how restrictions on advertising impact tobacco use and its associated behaviour, monitor tobacco industry activity, map vendors and access of products, and economic impact of restrictions on tobacco promotions at POS needs to be fulfilled. Without these measures it will be challenging to counter nefarious, cash-rich and truant tobacco industry.